OPTIMIZATION OF FERMENTATION PARAMETERS FOR ENHANCED PRODUCTION OF BIOETHANOL USING SACCHROMYCES CEREVISIAE - NYAMBEGA MORARO PATRICK; MUTHUSAMY PALANISWAMY (International Journal of Pharma and Bio Sciences, 2016)
Sugarcane bagasse is one of the most promising agricultural by-products for conversion to Biofuel. Ethanol fermentation has been achieved using an integrated process combining chemical pre-treatment by acid-alkali with enzymatic hydrolysis and fermentation. The pre-treated cellulosic residue was hydrolyzed by a crude enzyme preparation from Aspergillus flavus KUMBF1308 containing complimentary β– glucosidase activity. This study thus demonstrated the potential use of simple integrated process with minimal environmental impact, with the use of promising alternative on-site enzyme and yeast, for the production of ethanol from this lignocellulosic biomass. The assessment of a novel on-site enzyme preparation on bagasse was reported in combination with an environmentally friendly pre-treatment process. The enzymatic hydrolysis process was used in simultaneous saccharification and fermentation (SSF) processes for evaluating the convertibility of the cellulose and hemicellulose contained in sugarcane bagasse to ethanol. In this investigation bioethanol production was optimized by S. cerevisiae. After analysis the reducing sugar content of 52gL-1 was recorded, after 72h of incubation, the ethanol yield was maximum at pH 5.5, temperature 32°C and 10% inoculum level. The work thus demonstrated the potential of this alternative process for the production of cellulosic ethanol from bagasse.